Crystal and molecular structure determination, TGA-DTA, and infrared and Raman spectra of rubidium nitroprusside, Rb2[Fe(CN)5NO] - Soria, Delia Beatriz (1996)
The title compound, Rb2[Fe(CN)5NO], crystallizes in the space group P212121, witha=5.687(1),b=15.956(2),c=12.645(3) A, andZ=4. Anions are in equivalent C1 sites (one per asymmetric unit) and are slightly distorted octahedra (C4v ideal symmetry). TGA and DTA curves and vibrational (infrared and Raman) spectra of Rb2[Fe(CN)5NO] were obtained. Results are interpreted in view of the crystal structure of the compound and the behavior of related substances.